2023
DOI: 10.3390/foods12071358
|View full text |Cite
|
Sign up to set email alerts
|

Purple Wheat: Food Development, Anthocyanin Stability, and Potential Health Benefits

Abstract: Colored wheats such as black, blue, or purple wheat are receiving a great interest as healthy food ingredients due to their potential health-enhancing attributes. Purple wheat is an anthocyanin-pigmented grain that holds huge potential in food applications since wheat is the preferred source of energy and protein in human diet. Purple wheat is currently processed into a variety of foods with potent antioxidant properties, which have been demonstrated by in vitro studies. However, the health impacts of purple w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 91 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…In recent years, wheat breeding has been focused on accumulating anthocyanin compounds in the grain, which can improve food quality and human health [33][34][35]. Previous studies have revealed that anthocyanins remain stable during bread production [43,44] and can be easily incorporated into human diet by using purple grain in bakery products [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, wheat breeding has been focused on accumulating anthocyanin compounds in the grain, which can improve food quality and human health [33][34][35]. Previous studies have revealed that anthocyanins remain stable during bread production [43,44] and can be easily incorporated into human diet by using purple grain in bakery products [42].…”
Section: Discussionmentioning
confidence: 99%
“…We investigated wheat bran extract as a natural source of anthocyanins, which can be regularly consumed by incorporating purple grain into bread preparation without any additional additives or supplements [42]. Previous studies have demonstrated that anthocyanins remain intact during bread production [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, breeding for the anthocyanins content in wheat grains has become a focus [ 11 ] as anthocyanin-rich cultivars have shown to be very promising as functional foods [ 12 , 13 ]. The development of biofortified colored wheat adds nutritional and functional health benefits to the energy-rich wheat.…”
Section: Introductionmentioning
confidence: 99%